The Illusion of Local Autonomy: Central Power and Subnational Governance in Indonesia - Maria Lusiana Florentin Werang; Nicolaus Petrus Likuwatan Werang; Mia Rizki; Rizky Amalia Putri (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2026)
Decentralization has been a key reform agenda in Indonesia since the post-1998 transition, aiming to scale up democratic governance and reduce regional disparities. While assumptions about (central) authority lead to a linear transfer of authority, this article argues that decentralization has produced a counterintuitive configuration, best understood as a recentralization of bureaucracy within a formally decentralized system. This connectivity emphasizes that local governments retain administrative responsibilities, while the central government reasserts control through regulatory, fiscal, and sectoral instruments. Further, qualitative content analysis and data collection, guided by iterative coding and triangulation, are applied to laws, implementing regulations, policy documents, and peer-reviewed literature to explore how authority is distributed and reconfigured across levels of government. Findings suggest that variations in governance are insignificant and reflect local capacity, which is inherently part of decentralization, rather than a strategic reconfiguration of authority in which high-risk functions are administrative burdens and then delegated. It has resulted in overlapping mandates, fragmented accountability, and consistently uneven concretization since the reform era. This article also reframes Indonesian decentralization as an evolving institutional solution formulated by selective recentralization. It suggests that reforms should prioritize clarifying authority and strengthening accountability rather than relying solely on capacity building.